2020
DOI: 10.1136/annrheumdis-2020-eular.4709
|View full text |Cite
|
Sign up to set email alerts
|

Ab1178 an Audit of Originator Adalimumab to Biosimilar Switch in Two Hospitals

Abstract: Background:Biological drugs have revolutionized the treatment of immune-mediated inflammatory diseases (IMIDs). Current guidelines reserve these drugs for patients with severe refractory disease.Biologic drugs are expensive, but as they reach patent expiry, the introduction of lower-cost biosimilars reduces their impact on health care budgets. It is estimated that NHS England could save £300 million by 2021 following the recent launch of adalimumab biosimilars [1]. As part of this process, there has been a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The rate of switching failure in our study was similar to that reported by Bergman et al [14] and higher than in other reports on psoriasis, rheumatoid arthritis, and Crohn's disease [13,[15][16][17]26]. Differences in these rates could be due to the different diseases included [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rate of switching failure in our study was similar to that reported by Bergman et al [14] and higher than in other reports on psoriasis, rheumatoid arthritis, and Crohn's disease [13,[15][16][17]26]. Differences in these rates could be due to the different diseases included [14].…”
Section: Discussionsupporting
confidence: 88%
“…Clinical trials and published evidence from actual clinical practice suggest that post non-medical switch, treatment discontinuation rates for adalimumab are variable (between 6.1% to 55.9%) [13][14][15][16][17]. In addition, there is little evidence collected on patients returning to their original treatment after switching to a biosimilar (switch back).…”
Section: Introductionmentioning
confidence: 99%